The silent legacy of COVID-19: exploring genomic instability in long-term COVID-19 survivors - Elaheh Abiri; Ali Abiri; Salman Daneshi; Rasoul Raesi (BMC Infectious Diseases)
Abstract Background Persistent symptoms and complications reported by many patients for more than four weeks after contracting coronavirus disease 2019 (COVID-19) are referred to as post-COVID-19 syndrome. These persistent symptoms can occur in individuals with both mild and severe COVID-19, though the underlying pathophysiological mechanisms remain poorly understood. This study aims to explore post-COVID-19 syndrome from a biological perspective, focusing on genomic instability. Methods In this cross-sectional study, the comet assay method was employed in March 2024 to evaluate the level of DNA damage in 29 patients to examine the post-COVID-19 syndrome state at Kausar Semnan Hospital in Iran. Levels of DNA damage were assessed using the alkaline comet assay in patients hospitalized for COVID-19, four weeks after a positive RT-PCR test. Patients were categorized based on pneumonia severity: mild (11 patients in non-ICU), moderate (10 patients in ICU and non-intubated), and severe/critical (8 patients in ICU and intubated). Ten healthy individuals who tested negative for COVID-19 were considered as a control group. Data were analyzed using descriptive and inferential statistical tests at a significance level of p < 0.01 in GraphPad Prism 9 software. Results Post-COVID-19 patients exhibited significantly higher levels of DNA damage compared to healthy controls. The highest DNA damage was observed in intubated-ICU patients (mean DNA damage: 29.5%), followed by non-intubated-ICU patients (mean: 24.3%), non-ICU patients (mean: 19.1%), and healthy controls (mean: 9.4%). These findings suggest a clear correlation between COVID-19 severity and increased genomic instability. Conclusion The results of this study highlight the prevalence of DNA damage in post-COVID-19 patients, which may explain long-term genomic instability and associated health complications. The findings underscore the importance of further research into the pathophysiological mechanisms of post-COVID-19 syndrome, particularly its impact on genomic stability. This study contributes to the growing evidence that post-COVID-19 syndrome is a complex condition with virus-specific abnormalities affecting multiple biological pathways. Future studies should focus on understanding these mechanisms to develop targeted interventions for long-term COVID-19 survivors.